2019
DOI: 10.32677/ijch.2019.v06.i06.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of specific learning disabilities among Gujarati medium primary school children

Abstract: Introduction: Learning disability in children is an assorted group of disorders where the individual unpredictably fails to proficiently attain, regain, and use information. Objective: The objective of this study was to measure the prevalence of specific learning disabilities (SpLDs) such as dyslexia and dysgraphia among the Gujarati medium primary schoolchildren. Methods: A cross-sectional study was conducted in public schools of Gujarati medium among children aged 7–12 years from the second, third, and fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“… 31 The least prevalence was reported as 1.58% by Arun et al 28 Mogasale et al reported 12.5%, 11.2%, and 10.5% prevalence of dysgraphia, dyslexia, and dyscalculia, respectively, 31 while the prevalence of SLD subtypes–dysgraphia, dyslexia, and dyscalculia–reported by Shan and Buch was 7.4%, 8.6%, and 7.1%, respectively. 32 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 31 The least prevalence was reported as 1.58% by Arun et al 28 Mogasale et al reported 12.5%, 11.2%, and 10.5% prevalence of dysgraphia, dyslexia, and dyscalculia, respectively, 31 while the prevalence of SLD subtypes–dysgraphia, dyslexia, and dyscalculia–reported by Shan and Buch was 7.4%, 8.6%, and 7.1%, respectively. 32 …”
Section: Resultsmentioning
confidence: 99%
“…The studies assessed children at a younger age itself, except for Arun et al, for which the age group was 12 to 19 years. Three studies assessed the subcategories of SLD separately along with the total prevalence of SLD [31][32][33] ; all other studies assessed SLD in total and not the subtypes. The study by Arora et al was done in the community setting, 29 and all the other studies were conducted at schools.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations